Systematic assessment of surgical complications in laparoscopically assisted vaginal hysterectomy for pelvic organ prolapse. (November 2015) - Mothes, Anke R.; Radosa, Marc P.; Runnebaum, Ingo B.
Abstract: Objective: To assess patient safety and complication rates in native tissue vaginal prolapse repair combined with laparoscopically assisted vaginal hysterectomy and prophylactic salpingectomy/salpingoophorectomy. Study design: This was a single-centre retrospective study conducted at the University Hospital, Urogynaecological Unit, with a certified urogynaecological surgeon. A cohort of 321 consecutive patients received laparoscopically assisted vaginal hysterectomy for pelvic organ prolapse grade II–IV combined with defect-specific vaginal native tissue repair. Analysis of the total cohort and subgroups according to prolapse grade and concomitant laparoscopic procedures was performed. Student's t -tests and chi-squared tests were used for descriptive statistical analysis. Surgical complications were classified using the Clavien–Dindo (CD) classification system of surgical complications. Results: Complications were classified as CD I (1.87%), CD II (13.39%), CD IIIa (0.62%), and CD IIIb (1.87%); no CD IV or CD V complication occurred. One (0.31%) intraoperative bladder lesion, but no rectal lesion, ureter lesion, or intraoperative haemorrhage requiring blood transfusion, was noted. The overall morbidity rate, including the intraoperative bladder lesion and the CD I complication, was 18.06%. All ( n  = 321) patients underwent prophylactic salpingectomy. Additional oophorectomy was performed in 222 post-menopausal patients. Pelvic adhesions were found in 123 (38.31%) patients and 148 (46%) patients presented grade IV prolapse. Operating time was longer for grade IV than for grade II/III prolapse ( p  < 0.01), but CD III complication rates did not differ between these groups. Operating time was longer when laparoscopic adhesiolysis was performed ( p  = 0.025), but this factor did not affect CD III complication rates. Conclusions: The combination of vaginal site-specific prolapse repair with laparoscopically assisted hysterectomy leads to low complication rates. Prophylactic salpingectomy or salpingoophorectomy can be performed safely in combination with hysterectomy for pelvic organ prolapse. In terms of surgical safety laparoscopy seems to be a meaningful addition to vaginal native tissue prolapse surgery.